HUBUNGAN KEMAMPUAN ADAPTASI DAN TEMPAT TINGGAL DENGAN TINGKAT DEPRESI PADA MAHASISWA BARU: Relationships on Adaptation Abilities and Residence With Depression Levels in New Students - Ajeng Febrianti Rahayu; Bagas Aidi; Meirna Mega Rizki; Ayik Mirayanti Mandagi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2021)
ABSTRACTFirst year student are one of the groups that are prone to depression. This is because the first year student is in a transition period or in a new condition that initially senior high school student becomes a college student. In addition, busy schedules, new learning environments and homesickness can trigger depression in college students. This study used a cross sectional study design. Respondents in this study were new students of the Study Program Outside the Main Campus (PSDKU) of Airlangga University in Banyuwangi, class 2019 with a total of 110 students. Depression levels were obtained from the Beck Depression Inventory (BDI-II) questionnaire. Meanwhile, the adaptability was obtained from the Communicative Adaptability Scale (CAS) questionnaire and the place of residence was obtained from questions about where to live during college. A total of 53 out of 110 students (49,1%) experienced low depression and students who experienced high depression were 57 out of 110 students (50,9%). The results of the chi square test regarding the relationship between residence and the level of depression of new students, obtained data p= 0.008 (p <0.05). Chi-square test results regarding the relationship between adaptation ability and depression level of new students, obtained data p = 0.001 (p <0.05). There is a relationship between residence and adaptability with the degree of depression of new students. Higher education institutions are expected to pay more attention to the psychological conditions of students and new students are expected to maintain good coping management in facing the new environment.Keywords: depression level, adaptability, place to live, new students ABSTRAKMahasiswa baru adalah salah satu kelompok yang rentan mengalami depresi. Hal ini dikarenakan mahasiswa baru berada pada masa transisi atau suatu kondisi baru yang awalnya siswa SMA menjadi mahasiswa. Selain itu, jadwal yang padat, lingkungan belajar yang baru dan homesickness dapat memicu depresi pada mahasiswa. Penelitian ini menggunakan desain penelitian crosssectional. Responden pada penelitian ini yaitu mahasiswa baru Program Studi Diluar Kampus Utama (PSDKU) Universitas Airlangga di Banyuwangi angkatan 2019 dengan jumlah 110 mahasiswa. Tingkat Depresi didapatkan dari kuisioner Beck Depression Inventory (BDI-II). Sedangkan kemampuan adaptasi didapatkan dari kuisioner Communicative Adaptability Scale (CAS) dan tempat tinggal didapatkan dari pertanyaan mengenai tempat tinggal selama kuliah. Sebanyak 49,1% (53 dari 110 mahasiswa) mengalami depresi ringan dan mahasiswa yang mengalami depresi berat sebanyak 50,9 (57 dari 110 mahasiswa). Hasil uji chisquare mengenai hubungan tempat tinggal dengan tingkat depresi mahasiswa baru, diperoleh data p=0,008 (p<0,05). Hasil uji chisquare mengenai hubungan kemampuan adaptasi dengan tingkat depresi mahasiswa baru, diperoleh data p=0,001(p<0,05). Terdapat hubungan antara tempat tinggal dan kemampuan adaptasi dengan tingkat depresi mahasiswa baru. Institusi perguruan tinggi diharapkan lebih memperhatikan kondisi psikologis mahasiswa dan mahasiswa baru diharapkan tetap mempertahankan manajemen koping yang baik dalam menghadapi lingkungan baru.Kata Kunci: tingkat depresi, kemampuan adaptasi, tempat tinggal, mahasiswa baru